Income Polarization in the United States - Alichi, Ali (IMF Working Papers; Working Paper ;, 2016)
The paper uses a combination of micro-level datasets to document the rise of income polarization-what some have referred to as the 'hollowing out' of the income distribution-in the United States, since the 1970s. While in the initial decades more middle-income households moved up, rather than down, the income ladder, since the turn of the current century, most of polarization has been towards lower incomes. This result is striking and in contrast with findings of other recent contributions. In addition, the paper finds evidence that, after conditioning on income and household characteristics, the marginal propensity to consume from permanent changes in income has somewhat fallen in recent years. We assess the potential impacts of these trends on private consumption. During 1998-2013, the rise in income polarization and lower marginal propensity to consume have suppressed the level of real consumption at the aggregate level, by about 3 1\2 percent-equivalent to more than one year of consumption.